2012
DOI: 10.1186/2193-1801-1-40
|View full text |Cite
|
Sign up to set email alerts
|

Tracing contacts of TB patients in Malaysia: costs and practicality

Abstract: Tuberculin skin testing (TST) and chest X-ray are the conventional methods used for tracing suspected tuberculosis (TB) patients. The purpose of the study was to calculate the cost incurred by Penang General Hospital on performing one contact tracing procedure using an activity based costing approach. Contact tracing records (including the demographic profile of contacts and outcome of the contact tracing procedure) from March 2010 until February 2011 were retrospectively obtained from the TB contact tracing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Analyses of the health system costs of contact screening and diagnosing and treating tuberculosis infection from Uganda, Malaysia, and Vietnam suggest that this is a highly feasible target. 22 , 23 , 24 If in a particular setting the costs of intervention exceed this amount, then a priority task becomes how to deliver the necessary interventions more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the health system costs of contact screening and diagnosing and treating tuberculosis infection from Uganda, Malaysia, and Vietnam suggest that this is a highly feasible target. 22 , 23 , 24 If in a particular setting the costs of intervention exceed this amount, then a priority task becomes how to deliver the necessary interventions more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…The total provider sector cost was the sum of outpatient clinic costs (i.e., the sum of human resource cost, capital cost, electricity cost and consumables cost), hospitalization costs, chest X-ray costs (i.e., the sum of human resource cost, capital cost, electricity cost and consumables cost [ 23 , 24 ]), laboratory services costs (i.e., the sum of human resource cost, capital cost, electricity cost and consumables cost) and medicines costs of all patients included in the study. The average provider sector cost was obtained by dividing the total provider cost by the number of successfully treated patients.…”
Section: Methodsmentioning
confidence: 99%
“…The personnel time cost for each of the employees involved was calculated according to the pay scale of the Federal Civil Services Officers under the System of Remuneration Malaysia [ 25 ]. Prior to the calculation, these salaries were converted into the salary per minute (MYR/min) by assuming a daily working time of 8 hours and a monthly working time of 20 days [ 23 , 24 ]. The cost of each employee per single activity was obtained by multiplying the mean time (minutes) spent by that employee doing a specific activity by his/her salary per minute.…”
Section: Methodsmentioning
confidence: 99%
“…According to the Malaysian Clinical Practice Guidelines for TB, a child contact must be screened within 6 weeks of diagnosis of the index case [9]. However, previous studies conducted in Malaysia have revealed that most diagnosed TB cases remain heavily dependent on passive case detection, where patients have already developed sufficiently significant symptoms spurring them to seek medical treatment [10]. This is an undesirable outcome for any NTP, as TB is still prevalent in the country.…”
Section: Introductionmentioning
confidence: 99%